Convective drying of cambuci, a native fruit from the Brazilian Atlantic Forest: Effect of pretreatments with ethanol and freezing - Rojas M.L. (2021)
The authors are grateful to the S?o Paulo Research foundation (FAPESP, Brazil): projects n? 2014/12606-3 and 2019/05043-6; GR Carvalho post-doctoral fellowship (2018/17844-0); the ?Coordena??o de Aperfei?oamento de Pessoal de N?vel Superior?Brasil (CAPES)?: BO Gomes (88887.485030/2020-00), JS Guedes (88887.513566/2020-00) and KC Santos (88882.378385/2019-01) M.Sc. and Ph.D. Scholarships; the National Council for Scientific and Technological Development (CNPq, Brazil): BS Bitencourt (132297/2019-1) M.Sc. Scholarship and PED Augusto productivity grant (310839/2020-3); the Fondo Nacional de Desarrollo Cient?fico, Tecnol?gico y de Innovaci?n Tecnol?gica (FONDECYT, Peru) from the ?Consejo Nacional de Ciencia, Tecnolog?a e Innovaci?n Tecnol?gica? (CONCYTEC, Peru): project n? 409-2019-FONDECYT; the Universidad Privada del Norte (UPN, Peru): project n? 20201005. The authors are also grateful for the valuable help of B.Sc. Isabela Silveira and N?colas Gon?alves Borrego, as well as Mr. Paulo Nakanishi from ?Sitio Recanto dos P?ssaros? for providing the fruits.